Conciencia sinodal en los sínodos de los siglos II-IV (2022)
The article studies the synodal awareness of the Church as expressed in the documents - including synodal letters, canons, and ancient accounts - of all the synods we know about through to the First Council of Constantinople (381). During the first centuries of its history, the synods were a crucial way of living and expressing the synodality of the Church. The study of ecclesiological nature considers three aspects that are very present in antiquity and important for renewing synodal awareness today: the joint discernment of the truth of the faith, the reception of synods as a criterion of authenticity, and the intrinsic relationship between synodality and primacy.